Analytical estimation of the distribution of thermal neutron flow; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Gvozdyakov D. V. Dmitry Vasilievich; Matveev A. S. Aleksandr Sergeevich; Tanishev A. O. Anton; Shvab S. A. Svetlana (2017, 2017)
Title screen